Functional antibodies against G-protein coupled receptors in Beagle dogs infected with two different strains of Trypanosoma cruzi - Wallukat, Gerd; Botoni, Fernando Antônio; Rocha, Manoel Otávio da Costa; Louise, Vitória; Müller, Johannes; Talvani, Andre (Frontiers in Immunology, 2022)
The interaction of the anti-beta1-adrenergic receptor autoantibodies (β1ARAb) and the anti-muscarinic M2 receptor autoantibodies (M2RAb) with cardiac neurotransmitter receptors were identified in human chronic Chagas cardiomyopathy (CCC) related to the ECG and dysautonomia disturbances. Dogs are considered gold model to the study of Trypanosoma cruzi infection due the clinical similarities with CCC. This study aims to evaluate whether anti-β1ARAb, anti-β2ARAb, and anti-muscarinic M2RAb are generated in Beagle dogs infected by T. cruzi using Y and Berenice-78 strains of T. cruzi. Animals were infected with 4.0 x 103 bloodstream trypomastigotes/kg of body weight and, after 25 months of infection, blood sample was collected, and serum stored at -80oC. Dog serum was treated by ammonium sulphate precipitation and the IgG antibodies isolated and added to the beating neonatal rats’ cardiomyocytes. All T. cruzi-infected dogs developed agonistic β1ARAb, β2ARAb, and M2RAb. Animals infected by Berenice strain presented less β2ARAb and M2RAb activities than dogs infected by Y strain of the parasite. In cardiomyocytes culture, the antibodies recognized an epitope on the second extracellular loop of the receptors which were similar to findings in human Chagas disease. There was no detection of antibody against G protein-coupled receptor in serum from uninfected dogs. In conclusion, both Y and Berenice-78 strains of T. cruzi induced dog antibodies, whose targets located in the second extracellular loop of the adrenergic and muscarinic receptors were similar to those observed in individuals with CCC. Therefore, our findings highlight dogs as a promisor model to investigate pathogenic roles of functional Ab against G-protein coupled receptors.